Effect of supervised exercise on physical function and balance in patients with intermittent claudication. Issue 4 (3rd February 2014) - Mockford, K A; Gohil, R A; Mazari, F; Khan, J A; Vanicek, N; Coughlin, P A; Chetter, I C
Abstract: Background: The aim of the study was to identify whether a standard supervised exercise programme (SEP) for patients with intermittent claudication improved specific measures of functional performance including balance. Methods: A prospective observational study was performed at a single tertiary vascular centre. Patients with symptomatic intermittent claudication (Rutherford grades 1–3) were recruited to the study. Participants were assessed at baseline (before SEP) and 3, 6 and 12 months afterwards for markers of lower-limb ischaemia (treadmill walking distance and ankle : brachial pressure index), physical function (6-min walk, Timed Up and Go test, and Short Physical Performance Battery (SPPB) score), balance impairment using computerized dynamic posturography with the Sensory Organization Test (SOT), and quality of life (VascuQoL and Short Form 36). Results: Fifty-one participants underwent SEP, which significantly improved initial treadmill walking distance ( P = 0·001). Enrolment in a SEP also resulted in improvements in physical function as determined by 6-min maximum walking distance ( P = 0·006), SPPB score ( P < 0·001), and some domains of both generic (bodily pain, P = 0·025) and disease-specific (social domain, P = 0·039) quality of life. Significant improvements were also noted in balance, as determined by the SOT ( P < 0·001). Conclusion: Supervised exercise improves both physical function and balance impairment. Abstract : Better balance